TINJAUAN TENTANG MOTORIK KASAR MURID TAMAN KANAK-KANAK DHARMA WANITA PAINAN SELATAN KABUPATEN PESISIR SELATAN - Gustian Indra; Gusril Gusril (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
Kindergarten Students This study began with the unknown of gross motor skills of young children in the South Painan Kindergarten Dharma Wanita Selatan Pesisir South District. The purpose of this study was to reveal the gross motor skills of early childhood in the kindergarten. This type of research is descriptive. The population in this study were 45 people from 20 men and 25 women in the Dharma Wanita Kindergarten in South Painan District. Sampling using a total sampling technique. The gross motor ability assessment instrument is measured in 6 test forms, namely jumping forward with two feet, walking on tiptoes with fingertips, motion of an airplane, throwing a ball with one hand, and catching the ball with two hands. This motion is grouped into 3 categories, namely non-locomotor, locomotor, and manipulative motion abilities by looking at the norm tests for gross motor ability assessment in the form of percentages. Based on the analysis of the data obtained from the results of the study of 31 children, a total of 3 children developed very well criteria (BSB), 7 children developed criteria as expected (BSH), 9 children began to develop criteria (MB), and 12 children had criteria developing (BB). Based on the results of the study, it can be concluded that the gross motor skills of children in the South Painan Kindergarten Dharma Wanita South Pesisir South Regency are under-developed criteria (BB).